Immunotherapy in Radioactive Iodine Refractory Thyroid Cancer – Case Report and Review of Literature - Muhtasim, Muhammad Farhan; Persi, Abdullah Al; Khan, Mahjabin Nobi; Alim, Noor E Amrin; Hossain, Mohammad Sazzad; Akhter, Anjuman Ara; Bhattacharjee, Pabitra Kumar (Bangladesh Journal of Nuclear Medicine, 2024)
The therapeutic approach to radioiodine-refractory advanced differentiated thyroid cancer has undergone significant advancements in recent years, leading to a paradigm shift in its management protocol. Despite being recognized for its favorable prognosis, 15.25% of cases continue to defy conventional treatment. In recent times, cancer immunotherapy has been revolutionized by the approval of immune checkpoint blockade therapies, including anti-angiogenic multi-kinase inhibitors and fusion-specific kinase inhibitors. However, none of these treatments are curative, and most patients eventually show disease progression. Therefore, contemporary research is now focused on detecting resistance mechanisms to these agents. This case report discusses the progression of a radioiodine-refractory advanced DTC patient who received conventional management followed by two multi-kinase inhibitors, Lenvatinib and Cabozanitib. Consequently, the prognosis was assessed using biochemical, genetic, and clinical findings. Bangladesh J. Nuclear Med. 26(2): 218-225, 2023